Development stages of ESP in teaching English in Uzbekistan (Texas Journal of Multidisciplinary Studies, 2024)
In this article, opinions are given about the implementation of ESP in Uzbekistan, its importance for representatives of various fields. Also, the work of the President of the Uzbekistan focusing on the development of foreign languages is briefly covered.